E-learning Development for Improving English Learning Motivation in High Schools - Yoka Larasati Fatikhaningrum; Haryanto (Universitas Pendidikan Ganesha, 2025)
English is an important foreign language to master in education; however, its learning is often considered difficult and lacks student motivation. This study aimed to develop and evaluate the effectiveness of a website based English e-learning platform to enhance interactivity and student learning motivation. The study employed a Research and Development (RnD) approach using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of students as end users, while the feasibility assessment was conducted by material and media experts. Data were collected through observation, interviews, and questionnaires, then analyzed descriptively to assess the feasibility and effectiveness of the e-learning platform. The results indicated that the website-based e-learning product is feasible for use, with expert evaluations ranging from “Good” to “Very Good.” User trials yielded an average score of 90.6, demonstrating that the platform is effective in increasing learning motivation. Functionally, the e-learning platform can serve as a supplement, complement, or substitution for face to face learning. In conclusion, the development of the website based learning media using the ADDIE model proved to be effective, practical, and capable of enhancing student motivation. The implications suggest that this platform can be used as an alternative interactive and flexible digital learning strategy and serves as a foundation for developing similar learning media for other subjects.